Factors affecting the transition from university to work in selected Malaysian cities: is a public university degree a disadvantage? - Cheong, Jia Qi; Suresh Narayanan (2020)
Massive investments in higher education have witnessed a proliferation of public and private universities in Malaysia. A parallel development of concern is the view that public university graduates are finding it more difficult than their private university counterparts in transiting from university to work. To test the empirical veracity of this widely expressed belief, data from 441 currently employed graduates from three major urban centres were analysed to determine factors that increased the probability of securing permanent employment within six months of graduation, the officially used cut-off period. While the findings indicated that the transition is eased largely by personal endeavours (other than being Chinese) such as mastering English, attaining a high GPA, and participating in extracurricular activities, we also found a negative association between having a public university qualification and the length taken to secure the first permanent job. We discuss the implications of these findings for Malaysian education policy. If a public university degree indeed disadvantages a graduate in transiting to work, it would undermine the role of public universities as avenues for the upward social mobility of students from disadvantaged backgrounds. Additionally, the large expenditures on public universities would appear to be misallocated.